Current Efforts in the Development of Vaccines for the Prevention of Zika and Chikungunya Virus Infections - Schrauf, Sabrina; Tschismarov, Roland; Tauber, Erich; Ramsauer, Katrin (Frontiers in Immunology, 2020)
Arboviruses represent major challenges to public health, particularly in tropical and subtropical regions, and a substantial risk to other parts of the world as respective vectors extend their habitats. In recent years, two viruses transmitted by Aedes mosquitoes, Chikungunya and Zika virus, have gathered increased interest. After decades of regionally constrained outbreaks, both viruses have recently caused explosive outbreaks on an unprecedented scale, causing immense suffering and massive economic burdens in affected regions. Chikungunya virus causes an acute febrile illness that often transitions into a chronic manifestation characterized by debilitating arthralgia and/or arthritis in a substantial subset of infected individuals. Zika infection frequently presents as a mild influenza-like illness, often subclinical, but can cause severe complications such as congenital malformations in pregnancy and neurological disorders, including Guillain‒Barré syndrome. With no specific treatments or vaccines available, vector control remains the most effective measure to manage spread of these diseases. Given that both viruses cause antibody responses that confer long-term, possibly lifelong protection and that such responses are cross-protective against the various circulating genetic lineages, the development of Zika and Chikungunya vaccines represents a promising route for disease control. In this review we provide a brief overview on Zika and Chikungunya viruses, the etiology and epidemiology of the illnesses they cause and the host immune response against them, before summarizing past and current efforts to develop vaccines to alleviate the burden caused by these emerging diseases. The development of the urgently needed vaccines is hampered by several factors including the unpredictable epidemiology, feasibility of rapid clinical trial implementation during outbreaks and regulatory pathways. We will give an overview of the current developments.